Immunogenicity of Infanrix™ hexa administered at 3, 5 and 11 months of age - Van Der Meeren, Olivier; Kuriyakose, Sherine; Kolhe, Devayani; Hardt, Karin (Vaccine, 2012)
A pooled analysis of data from four vaccination studies conducted in Europe was undertaken to assess the immunogenicity of Infanrix™ hexa (DTPa–HBV–IPV/Hib, GlaxoSmithKline Biologicals) when administered in a total of 702 healthy infants at 3, 5 and 11–12 months of age. One month after dose 2, between 96.3% and 100% of subjects had seroprotective antibodies against diphtheria, tetanus, hepatitis B and poliovirus types 1, 2 and 3; 91.7% against Hib and ≥99.0% were seropositive for each pertussis antigen. One month after the third dose, 98.9–100% of subjects were seroprotected/seropositive for all vaccine antigens. Geometric mean antibody concentrations/titres for each vaccine antigen increased by 6.7–52.9 fold after the third vaccine dose. No serious adverse events in DTPa–HBV–IPV/Hib recipients were vaccine related. Infanrix™ hexa induces an adequate immune response after 2-dose primary plus booster doses when administered according to a 3, 5 and 11 months schedule.